Extraction the spatial data from motion data using the convolutional neural network - ดวงกลาง ภูมิพัฒน์; แก้วเหลี่ยม ศุภกานต์ (NKRAFA JOURNAL OF SCIENCE AND TECHNOLOGY, 2020)
The Royal Thai Air Force has an aerial imaging and recording system using Forward Looking Infrared (FLIR) capable of both day and night operations. The motion data will be sent to the ground station via Video Down Link (VDL). This method allows users to analyse image data realtime during the mission. However, the display of motion data on Geographic Information System still has limitations and requires specialised programs, which produce additional procurement costs. Therefore, the research team has devised an option to develop an image display system from aircraft to analyse data on Geographic Information System to track aircraft during the mission. The research team applied a Convolution Neuron Network to create a model for tracking aircraft by analysing spatial data from motion data during flight missions on Geographic Information System.